Randomized controlled trial of an E-learningprogram for physiotherapy students to improve the management of rotator cuff related shoulder pain: a study protocol - AYBERK, BAHAR; POLAT, MİNE GÜLDEN (My University, 2022)
Background:The majority of shoulder complaints are occurred due to rotator cuff pathologies. Although conservative treatments including physiotherapy are acknowledged as the first-line treatment approach in the management of shoulder pain, the uptake of physiotherapy practice is variable. One possible explanation of this could be the poor evidence-based knowledge mobilization to practice. The aim of the study was to evaluate the efficacy of an E-learning program on physiotherapy students\" knowledge of evidence-based Rotator cuff-related shoulder pain (RCRSP) management and their confidence in applying this care compared to a control group.Methods:A randomized controlled study will be carried with 146 fourth-year physiotherapy students. Students will be assigned to one of two groups: E-learning (N=73) or control (N=73). The outcomes will be: (1) RCRSP knowledge and clinical reasoning skills, and (2) self-reported confidence in RCRSP knowledge and clinical reasoning abilities. Both measurements will be held at baseline and post-intervention.Conclusions:This is the first trial to investigate if a specifically designed E-learning program besides a regular learning curriculum, improves students’ knowledge and self-confidence in the RCRSP management. Enhancing students’ after-graduation readiness to manage patients with RCRSP may help to allow patients access to evidence-informed physiotherapists.Trial registration:This trial was registered on clinicalTrials.gov on 17 June 2021 (NCT04952623)KeywordsE-learning, Rotator cuff injuries, Physiotherapy education
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Chiropractics; Rehabilitation; Physical Therapy, Sports Therapy and Rehabilitation